Reduced Air Pollution during the Prevailing of COVID-19 Pandemic: Five Years Observation and Path Analysis in the Fenwei Plain, Northwest China - Yuanyuan Meng; Wanlong Sun (Advances in Meteorology)
Heavy pollution in North China has attracted extensive attention in recent decades, and numerous studies have been conducted in developed regions, while studies on the heavily polluted Fenwei Plain in Northwest China are still scarce. In this study, we analyzed the continuous air pollution records of Weinan city on the Fenwei Plain from 2016 to 2020 to provide specific prevention and control strategies for the region. From 2016 to 2020, pollutant concentrations showed an overall decreasing trend, with a slight increase in O3 concentration. The study found that during the COVID-19 lockdown period, O3 was also significantly affected by the lockdown policy. During the prevailing COVID-19 pandemic in 2020, anthropogenic emissions were reduced due to restraints on commercial and social activities. NO2 responds sensitively during COVID-19, and PM2.5 has a delayed response. We applied pathway analysis to investigate the contribution of different pollutants and meteorology to PM2.5. The results show that CO and NO2 have the largest positive comprehensive effect, while wind speed and temperature have the largest negative comprehensive effect. Spearman’s correlation analysis shows that NO2 contributes significantly to O3 production in different AQI ranges. We advocate that the NOx should be given more attention and become the new focus of air control.